Population crash of an endemic South African cyprinid: the role of non-native fish, drought and other environmental factors - Cerrilla, Cecilia (FitzPatrick Institute of African Ornithology, 2020)
Native freshwater fish are in decline worldwide due to human impacts including impoundment, changes to water quality, over-abstraction, climate change and the introduction of non-native species. South Africa's Cape Fold Ecoregion (CFE) harbours exceptionally high freshwater fish endemism, yet the majority of these species are threatened with extinction. The Clanwilliam sandfish (Labeo seeberi), an endangered cyprinid, has declined across its range in the CFE and currently exists in only a handful of tributaries of the Doring River in severely fragmented populations. The last remaining recruiting sandfish population occurs in the Oorlogskloof River, making this tributary one of critical conservation value. In this study, I analysed a six-year dataset comprising fish survey data from 38 sites along 25 km of the Oorlogskloof River to characterise spatio-temporal variation in sandfish abundance and size structure and evaluate the relative influence of different environmental factors on sandfish population trends. The environmental factors considered included other fish in the system, especially three non-native fishes (banded tilapia Tilapia sparrmanii, smallmouth bass Micropterus dolomieu and bluegill sunfish Lepomis macrochirus), temperature, precipitation, habitat characteristics and a range of physicochemical factors. The results show that sandfish have experienced a 93% decline in the sampled stretch of the Oorlogskloof River since 2013 and that the ongoing drought may be preventing recovery. They also suggest that banded tilapia do not adversely affect the Oorlogskloof River sandfish population, while predation of juveniles by smallmouth bass and/or bluegill sunfish apparently reduces the abundance of sandfish, especially of juveniles, where these non-native fish are present. Future studies should attempt to isolate the relative impacts of the different invasive fish species and examine habitat requirements of different sandfish life stages. Management of the river's sandfish population should focus on precautionary actions such as continued monitoring and landowner engagement, as well as clearing dams of non-native species high in the catchment, to prevent the further upstream invasion of smallmouth bass and bluegill sunfish. Proactive measures, such as eradicating smallmouth bass and bluegill sunfish from the Oorlogskloof River, are also necessary to restore connectivity of suitable sandfish habitat in the Doring River system.